(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2025)
Research has consistently shown that teachers’ understanding of Merdeka Curriculum and its components varies considerably. To address this issue, we conducted a community service program (PkM) which focused on reviewing learning outcomes (Capaian Pembelajaran/CP) and their association with literacy skills assessment in the Merdeka Curriculum. This PkM was conducted in collaboration with the Subang Regency office of Education (Diknas) through the Bahasa Indonesia Teachers Forum (MGMP Bahasa Indonesia). More than ninety Bahasa Indonesia teachers attended and actively participated in the program. The training began with a discussion of Phase D (covering grades VII, VIII, and IX of SMP/MTs/Package B Program) as a case example. Once participants had a clear understanding of the language elements and CP for Phase D, they engaged in critical analysis of exercises on the Minimum Competency Assessment (AKM) within the Merdeka Curriculum. The exercise focused in identifying the types and characteristics of literacy-based questions. At the conclusion of the session, participants received feedback on their critical analyses, followed by a reflection on the training process. From the reflectional activity at the end of the session, it becomes evident that the formulation of CP represents a set of complex elements that require deep understanding. In addition, the effort to align CP with literacy assessments is an even more demanding task. With this in mind, the current PkM focused only on reviewing CP and its connection to literacy skills assessment through brief critical analysis and exercises. These reflections suggest that while the current PkM provided starting point, a more systematic and continuous approach will be essential in ensuring that teachers are fully equipped to integrate CP with literacy assessments in practice.